Le fortificazioni ateniesi nell’età classica: note su alcuni horoi di interpretazione incerta - Marchiandi, Daniela Francesca (Axon, 2019)
The paper examines some Athenian horoi of uncertain interpretation. Specifically I refer to a series of three horoi inscribed with the letter κ (ca. 450 BC) and a fourth horos inscribed with the letter α (400-350 BC). The hypothesis is that the letters are to be recognised not as abbreviations, according to the current interpretation, but as letter-labels. The horoi would serve to mark the sectors in which urban fortifications were divided, according to what we know for other poleis of the Greek world since the classical period (Corinth, Smyrna, Stratonikeia, Kos). Precisely these comparisons lead us to believe that these subdivisions were functional to the organisation of the defence of the walls, the so called phylakē. Alternatively, it cannot be excluded that they should instead be explained in the framework of the organisation of the building works of the walls or of the management of their ordinary maintenance.